Commodity price shocks and the victory of Jair Bolsonaro in the 2018 presidential elections in Brazil - Marcolin, João Victor Sales (2021)
The ascension of far-right politicians and parties over the recent years has motivated research that set out to explain this trend as a consequence of economic variables. This research contributes to this debate by investigating the effect of negative shocks on the commodity trade on the support for Jair Bolsonaro in the Brazilian presidential election of 2018. First, we create a variable that measures the exposure of a given municipality to variation in international commodity prices. Then, we show that a fall in international commodity prices is associated with job loss in the commodity-producing sectors, and that a one-percent reduction in employment in commodity production is associated with an increase in Bolsonaros share of votes: 0.078 percentage point in the first round and 0.076 percentage point in the runoff. However, these results are not robust to the inclusion of the share of self-declared pentecostal evangelicals in the population. This suggests an interaction between economic anxiety and shifts in cultural values, in consonance with the literature on the ascension on the far-right in other countries.